A three-dimensional through-hole structure composite conductive film doped with CNT and MXene and a preparation method thereof

CN116230318BActive Publication Date: 2026-10-20SHENYANG AEROSPACE UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310040364.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-12
Publication Date
2026-10-20
Estimated Expiration
2043-01-12

AI Technical Summary

Technical Problem

氧化物导电膜是一种重要的光电材料,具有导电性优异、可见光区透明、紫外光区截止以及红外光区较高的反射率等特性,被广泛应用在太阳能电池、气体传感器、液晶显示器等领域;金属纳米材料导电薄膜具有良好的透光性、高导电性、低成本以及柔性可弯折等特点,被广泛应用在电极和光电器件领域;石墨烯导电薄膜具有优异的力学性能、电性能、热性能和光学性能,被广泛应用在电容电极、电磁屏蔽和压阻传感器等领域;碳纳米管(CNT)导电薄膜具有优异的导电性能、独特的微观形貌和结构特征,被广泛应用于储能电池技术、压阻传感器、智能材料和电子电器领域;过渡金属碳化物(MXene)导电薄膜具有高电导率、高灵敏度等优点,但其力学性能和耐疲劳性较差,容易破坏失效

Benefits of technology

[0030](1)本发明方法通过浸没非溶剂致相分离转化法的方法制备“掺杂CNT和MXene的三维贯穿孔结构复合导电薄膜”,通过特定的树脂材料得到三维贯穿孔结构框架,固定MXene的位置,使得MXene呈现为三维排布,实现MXene的分布相对均匀、位置相对稳定。由于相转化法制备的多孔膜具有“上表面多孔,下表面相对致密,孔隙为贯穿的指状孔,通水且拦截大分子”的特性,在以MXene/树脂多孔膜为基体,抽滤进一定量的CNT水分散液时,可以实现对多孔膜进行CNT填充,进而使得膜内部的导电网络分布的更加均匀紧密,且导电网络之间没有绝缘的树脂阻隔,留有微小孔隙,提高了复合导电薄膜的电导率。由于MXene/树脂多孔膜的贯穿孔结构将导电网络分割成无数个微小部分,多孔膜的树脂材料为导电网络提供了必要的力学支撑,保证了复合导电薄膜的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116230318B_ABST
    Figure CN116230318B_ABST
Patent Text Reader

Abstract

The application discloses a three-dimensional through-hole structure composite conductive film doped with CNT and MXene and a preparation method, belongs to the field of nano conductive films, and effectively improves the conductivity of the composite conductive film by the cooperation between the two-dimensional sheet structure of MXene and the one-dimensional linear structure of CNT, and solves the problems of loose internal conductive network distribution and poor conductive performance. According to different application fields, different base resins and different conductive material ratios are selected to prepare the three-dimensional through-hole structure composite conductive film doped with CNT and MXene suitable for different application fields, and the preparation method is simple, the success rate is high, the preparation process is safe and environment-friendly, the preparation cost is low, the material is saved, the finished product can be widely applied, and the three-dimensional through-hole structure composite conductive film doped with CNT and MXene has high operability and practicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nano-conductive thin films, specifically relating to a three-dimensional through-hole structure composite conductive thin film doped with CNTs and MXene and its preparation method. Background Technology

[0002] Conductive thin films are thin films that can conduct electricity and perform specific electronic functions, with a substrate thickness of 0.25 mm or less. Common conductive thin film preparation techniques include magnetron sputtering, chemical vapor deposition, sol-gel method, and direct film formation method. The direct film formation method includes vacuum filtration, spin coating / spraying, and electrophoretic deposition. Conductive thin films can be applied in fields such as electrode materials for supercapacitors, optoelectronic devices, energy storage batteries, smart materials, solar cell components, electromagnetic wave protection, and stress-strain sensors. Conductive thin films include several major categories such as oxide conductive thin films, metal nanomaterial conductive thin films, graphene conductive thin films, and carbon nanotube (CNT) conductive thin films. Oxide conductive films are important optoelectronic materials, possessing excellent conductivity, transparency in the visible light region, cutoff in the ultraviolet light region, and high reflectivity in the infrared light region. They are widely used in solar cells, gas sensors, liquid crystal displays, and other fields. Metal nanomaterial conductive films have good light transmittance, high conductivity, low cost, and flexibility, and are widely used in electrodes and optoelectronic devices. Graphene conductive films have excellent mechanical, electrical, thermal, and optical properties, and are widely used in capacitor electrodes, electromagnetic shielding, and piezoresistive sensors. Carbon nanotube (CNT) conductive films have excellent conductivity, unique microstructure, and structural features, and are widely used in energy storage battery technology, piezoresistive sensors, smart materials, and electronic appliances. Transition metal carbide (MXene) conductive films have advantages such as high conductivity and high sensitivity, but their mechanical properties and fatigue resistance are poor, making them prone to failure.

[0003] Most current conductive thin film materials are made from single materials, generally exhibiting the problem of "excelling in certain aspects but suffering significant defects in others." Composite materials, on the other hand, are new materials formed by macroscopically combining two or more materials with different properties through physical or chemical methods. They combine the advantages of each component, effectively improving the problem of significant performance defects in single materials. Composite conductive thin films prepared through composite methods can significantly improve the mechanical and electrical properties of the thin film, enabling applications in more fields and achieving more functions and roles. Summary of the Invention

[0004] To address the problems existing in current conductive films, this invention employs a novel preparation method to fabricate a three-dimensional through-hole structure composite conductive film doped with CNTs and MXene. This invention utilizes a specific resin structure to construct the three-dimensional through-hole structure, providing support for the CNTs and MXene, and effectively ensuring the uniformity of the conductive network distribution within the film, thus possessing significant practical application value. The method of this invention is characterized by high efficiency, convenience, safety, environmental friendliness, low cost, and excellent conductivity and mechanical properties.

[0005] The three-dimensional through-pore structure composite conductive film doped with CNTs and MXene described in this invention is composed of an MXene / resin porous membrane and a monodisperse aqueous solution of CNTs. Its preparation method includes the following steps:

[0006] Step 1: Add a certain amount of transition metal carbide (MXene) powder to an organic solvent and mix evenly. Then, perform ultrasonic exfoliation and high-speed centrifugation to obtain a high-concentration MXene dispersion.

[0007] Step 2: After vacuum drying a certain amount of resin and polyvinylpyrrolidone (PVP), add them to an organic solvent and stir magnetically. Then add the prepared high-concentration MXene dispersion and continue stirring until homogeneous to obtain an MXene / resin / PVP solution.

[0008] Step 3: Coat the MXene / resin / PVP solution onto a clean glass plate to form a thin film, then quickly immerse the glass plate in room temperature deionized water for soaking to obtain an MXene / resin porous membrane.

[0009] Step 4: Using MXene / resin porous membrane as the filtration substrate, 300-600 ml of CNT monodisperse aqueous solution is uniformly filtered into the MXene / resin porous membrane. After vacuum drying, a three-dimensional through-pore structure composite conductive film of a certain thickness of doped CNT and MXene is obtained.

[0010] The above-mentioned method for preparing a three-dimensional through-hole structure composite conductive thin film doped with CNTs and MXene, wherein:

[0011] In step 1, the transition metal carbide (MXene) is Ti3C2.

[0012] Step 1, the preparation process of the high-concentration MXene dispersion, specifically includes:

[0013] (1) Add a portion of organic solvent to a certain amount of MXene powder, grind it evenly to form a paste, then add another portion of organic solvent and stir evenly to obtain an MXene solution; the mass-volume ratio of MXene powder to organic solvent is 1:(2.11-2.85);

[0014] (2) The MXene solution was subjected to ultrasonic ablation at an ultrasonic power of 80W for 20-60 minutes;

[0015] (3) The ultrasonically treated MXene solution is centrifuged at 7000-10000 rpm for 20-30 min to remove the supernatant. The precipitate is a high-concentration MXene dispersion, which is then stored under argon gas for later use. The purpose of ultrasonication is not only to peel off single or few layers of MXene, but also to appropriately reduce the size of the MXene sheets to ensure the regularity of the pore structure of the MXene / resin porous membrane in subsequent steps.

[0016] In step 2, the resin is selected from polysulfone (PSU), polyurethane (TPU), polyvinylidene fluoride (PVDF), and soluble polyimide (PI); the mass ratio of resin to PVP is 1:(0.2-0.8); and the mass ratio of resin to organic solvent is 1:(3.1-9.1).

[0017] The preparation process of the MXene / resin porous membrane in steps 2-3 specifically includes:

[0018] (1) After vacuum drying a certain amount of resin and PVP, add it to an organic solvent and stir it with magnetic force at 60-80℃ to obtain a resin / PVP solution. Let it stand to defoam.

[0019] (2) Add the high-concentration MXene dispersion to the resin / PVP solution and stir magnetically at room temperature to obtain the MXene / resin / PVP solution; wherein the mass ratio of the high-concentration MXene dispersion to the resin / PVP solution is 5:(15-20).

[0020] (3) Using a coating machine, adjust the coating thickness to 0.1-0.15 mm, prepare a thin film of MXene / resin / PVP solution on a clean, scratch-free glass plate, quickly immerse the glass plate in deionized water at 30-40℃, wait for the film to fall off the glass plate, soak for 6-8 hours, and obtain MXene / resin porous membrane, transfer it to clean deionized water for storage.

[0021] In step 4, the method for preparing the monodisperse aqueous solution of CNTs refers to the preparation method in patent CN2012104391772 (Preparation method of temperature sensor based on three-dimensional network film of carbon nanotubes); the CNTs used are multi-walled carbon nanotubes with a diameter of 8-15nm and a length of 30-70μm; the thickness of the resulting three-dimensional through-hole structure composite conductive film of doped CNTs and MXene is 80-110μm.

[0022] In step 4, the vacuum degree of the vacuum drying oven is -0.06MPa, the drying temperature is 40-60℃, and the drying time is 1-2h.

[0023] In the steps described, the organic solvent is selected from N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), and 1-methyl-2-pyrrolidone (NMP).

[0024] The preparation steps of the three-dimensional through-pore structure composite conductive film doped with CNTs and MXene of the present invention involve an immersion non-solvent-induced phase separation and conversion method. This method has stringent requirements for material selection and proportioning. Therefore, one of the key points of the present invention lies in the selection and proportioning of the resin material in the "MXene / resin porous membrane". The material system selection includes:

[0025] (1) Selection of Resin Material: The preparation method of MXene / resin porous membrane is the immersion non-solvent phase separation conversion method. The resin material used in this preparation method must be soluble in organic solvents but insoluble in water, and the organic solvent and water must have excellent compatibility. Resin materials such as polysulfone (PSU), polyurethane (TPU), polyvinylidene fluoride (PVDF), and soluble polyimide (PI) can meet the requirements of being soluble in the specified organic solvent but insoluble in water, and the organic solvent and water must have excellent compatibility.

[0026] (2) Optimization of the ratio of resin material to pore expander PVP: PVP is highly soluble in water and organic solvents, making it an excellent choice for pore expanders. However, the ratio of resin material to PVP directly affects the porosity and mechanical properties of the porous membrane. Excessive PVP content leads to resin viscosity, slower phase transformation rate, and affects the pore size on the surface of the MXene / resin porous membrane, resulting in fewer through-pores inside the membrane. Insufficient PVP content fails to expand the pores, preventing the formation of through-pores and reducing the hydrophilicity of the MXene / resin porous membrane, thus affecting the subsequent vacuum filtration effect. Based on the material system selected in this invention, the optimized resin-to-PVP mass ratio is 1:(0.2-0.8).

[0027] (3) Selection of organic solvents for dissolving resin materials: Different types of solvents have different destructive effects on resin segments. Therefore, under the condition of "the same resin solid content, different types of organic solvents", the viscosity of the resulting MXene / resin / PVP solution is different, which in turn changes the rate of phase transformation and affects the skin thickness and surface pore size of the MXene / resin porous membrane. The organic solvents selected include N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), and 1-methyl-2-pyrrolidone (NMP). According to the material system selected in this invention, DMAc has the best overall performance, resulting in a porous membrane with lower density, higher porosity, and a three-dimensional through-pore structure while ensuring basic mechanical properties.

[0028] (4) Optimization of the resin to organic solvent ratio: The ratio of resin to organic solvent is affected by the type of resin material. Due to the different properties of the resin itself, the pore distribution, shape and porosity of the MXene / resin porous membrane prepared with the same ratio are different, resulting in significant differences in the performance of the final composite conductive film. Based on the material system selected in this invention, the optimized mass ratio of resin to organic solvent is 1:(3.1-9.1).

[0029] Compared with the performance and preparation technology of existing conductive thin films, the advantages and beneficial effects of this invention are as follows:

[0030] (1) The method of this invention prepares a "three-dimensional through-pore structure composite conductive film doped with CNTs and MXene" by immersion non-solvent-induced phase separation and transformation. A three-dimensional through-pore structure framework is obtained through a specific resin material, fixing the position of MXene and making MXene present in a three-dimensional arrangement, achieving a relatively uniform distribution and relatively stable position of MXene. Since the porous membrane prepared by the phase transformation method has the characteristics of "porous upper surface, relatively dense lower surface, and through-pores that are finger-like, allowing water to pass through and intercepting macromolecules", when a certain amount of CNT aqueous dispersion is filtered into the MXene / resin porous membrane as a substrate, CNT filling can be achieved in the porous membrane, thereby making the conductive network inside the membrane more uniform and compact, and there is no insulating resin barrier between the conductive networks, leaving micropores, which improves the conductivity of the composite conductive film. Since the through-pore structure of the MXene / resin porous membrane divides the conductive network into countless micro-parts, the resin material of the porous membrane provides the necessary mechanical support for the conductive network, ensuring the stability of the composite conductive film.

[0031] (2) In the “three-dimensional through-hole structure composite conductive film doped with CNT and MXene” prepared by the method of the present invention, the two-dimensional sheet structure of MXene and the one-dimensional linear structure of CNT work together to effectively improve the conductivity of the composite conductive film and solve the problem of loose distribution of conductive network inside the material and poor conductivity.

[0032] (3) The resins that can be used in the method of the present invention have different material properties, providing feasibility for the application of "three-dimensional through-hole structure composite conductive film doped with CNT and MXene" in different fields. Polysulfone (PSU) resin is an engineering plastic with excellent mechanical properties, high temperature resistance, and good thermal and dimensional stability. The composite conductive film prepared has high mechanical strength and can be applied in fields such as capacitor electrodes or load-bearing structure health monitoring. Polyurethane (TPU) resin has good resilience, chemical resistance, and excellent thermal insulation properties. The composite conductive film prepared has good tensile properties and can be applied in fields such as flexible wearable sensors. Polyvinylidene fluoride (PVDF) resin is an engineering plastic with multiple excellent properties such as elasticity, low weight, low thermal conductivity, high chemical corrosion resistance, high weather resistance, and heat resistance. The composite conductive film prepared can be applied in fields such as electronics and electrical appliances.

[0033] (4) The method of the present invention has high flexibility and freedom. Different matrix resins and different conductive material ratios can be selected according to different application fields to prepare "three-dimensional through-hole structure composite conductive films doped with CNT and MXene" suitable for different application fields. The preparation method is simple, has a high success rate, is safe and environmentally friendly, has low preparation cost and saves materials. The finished product has a wide range of applications and has high operability and practicality. It is worth promoting and applying widely. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the microstructure of the three-dimensional through-hole structure composite conductive film doped with CNTs and MXene prepared by the method of the present invention.

[0035] Figure 2 This is a stress-strain diagram of the three-dimensional through-hole structure composite conductive film doped with CNT and MXene in Embodiment 1 of the present invention during the stretching process. Detailed Implementation

[0036] The present invention will now be described in more detail with reference to the accompanying drawings.

[0037] The microstructure diagrams of the "three-dimensional through-hole structure composite conductive thin film doped with CNTs and MXene" prepared in Examples 1-3 of this invention are shown below. Figure 1 As shown.

[0038] Example 1

[0039] In this embodiment of the invention, the PSU resin is granules produced by BASF AG, Germany; the PVP resin is produced by Yatai United Chemical Co., Ltd.; the MXene powder is Ti3C2 with a particle size of 200 mesh produced by Forsmann Technology (Beijing) Co., Ltd.; the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 8-15 nm and a length of 50 μm produced by Zhongke Nanotech Co., Ltd.; and the N,N-dimethylacetamide (DMAc) solvent is produced by Sinopharm Chemical Reagent Co., Ltd.

[0040] A method for preparing a three-dimensional through-hole structure composite conductive film with PSU as the matrix resin and doped CNTs and MXene, the specific steps of which are as follows:

[0041] Step 1: Add 5 ml of DMAc to 94.7 mg of MXene powder, grind evenly to form a paste, then add 195 ml of DMAc and stir evenly to obtain an MXene solution; ultrasonically exfoliate the MXene solution at 80 W for 60 min, centrifuge the ultrasonically treated MXene solution at 10000 rpm for 30 min, remove the supernatant, and the precipitate is a high-concentration MXene dispersion, which is stored under argon gas for later use;

[0042] Step 2: After vacuum drying 20g of PSU and 4g of PVP, add them in portions to 62g of DMAc. Stir at 80℃ to obtain a PSU / PVP solution. After standing to remove foam, add 5g of high-concentration MXene dispersion to 15g of PSU / PVP resin solution. Stir at room temperature until the mixture is homogeneous to obtain an MXene / PSU / PVP solution.

[0043] Step 3: Using a coating machine, adjust the coating thickness to 0.15 mm, coat the prepared MXene / PSU / PVP solution onto a clean, scratch-free glass plate to prepare a thin film, quickly immerse the glass plate in deionized water at 40°C, wait for the film to detach from the glass plate, soak for 8 hours to obtain an MXene / PSU porous membrane, transfer it to clean deionized water for storage and later use.

[0044] Step 4: Using an MXene / PSU porous membrane as the filtration substrate, 300 ml of CNT monodisperse aqueous solution was uniformly filtered into the MXene / PSU porous membrane using a vacuum filter. After filtration, the membrane was placed in a vacuum drying oven for vacuum drying to obtain a "three-dimensional through-pore structure composite conductive film doped with CNT and MXene" with a thickness of 110 μm and PSU as the matrix resin. The vacuum degree of the vacuum drying oven was -0.06 MPa, the drying temperature was 40℃, and the drying time was 2 h. The method for preparing the CNT monodisperse aqueous solution was adopted from the preparation method in patent CN2012104391772.

[0045] The stress-strain diagram of the "three-dimensional through-hole structure composite conductive film doped with CNTs and MXene" prepared in Example 1 of this invention during the stretching process is shown below. Figure 2 As shown, PSU resin is an engineering plastic with excellent mechanical properties but poor tensile properties, leading to fracture damage even with minor deformation. The composite conductive film prepared using the phase inversion method has a porous structure, which significantly improves its tensile properties. For example... Figure 2 As shown, within the strain range of 0-16%, the stress applied to the film exhibits a stable linear change, effectively improving the problem of poor tensile deformation of the film and broadening the application fields of the film.

[0046] Example 2

[0047] In this embodiment of the invention, the TPU resin is a powder produced by BASF AG, Germany; the PVP resin is produced by Yatai United Chemical Co., Ltd.; the MXene powder is Ti3C2 with a particle size of 200 mesh produced by Forsmann Technology (Beijing) Co., Ltd.; the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 8-15 nm and a length of 50 μm produced by Zhongke Nanotech Co., Ltd.; and the N,N-dimethylacetamide (DMAc) solvent is produced by Sinopharm Chemical Reagent Co., Ltd.

[0048] A method for preparing a three-dimensional through-hole structure composite conductive film with TPU as the matrix resin and doped with CNTs and MXene, the specific steps of which are as follows:

[0049] Step 1: Add 3 ml of DMAc to 52.6 mg of MXene powder, grind evenly to form a paste, then add 147 ml of DMAc and stir evenly to obtain an MXene solution; ultrasonically exfoliate the MXene solution at 80 W for 20 min, centrifuge the ultrasonically treated MXene solution at 7000 rpm for 20 min, remove the supernatant, and the precipitate is a high-concentration MXene dispersion, which is stored under argon gas for later use;

[0050] Step 2: After vacuum drying 30g of TPU and 24g of PVP, add them in portions to 273g of DMAc. Stir at 60℃ to obtain a TPU / PVP solution. After standing to defoam, add 5g of high-concentration MXene dispersion to 20g of TPU / PVP resin solution. Stir at room temperature until the mixture is homogeneous to obtain an MXene / PSU / PVP solution.

[0051] Step 3: Using a coating machine, adjust the coating thickness to 0.1 mm, apply the prepared MXene / TPU / PVP solution to a clean, scratch-free glass plate to prepare a thin film, quickly immerse the glass plate in 30°C deionized water, wait for the film to detach from the glass plate, soak for 6 hours to obtain an MXene / TPU porous membrane, transfer it to clean deionized water for storage and later use.

[0052] Step 4: Using an MXene / TPU porous membrane as the filtration substrate, 600 ml of CNT monodisperse aqueous solution was uniformly filtered into the MXene / TPU porous membrane using a vacuum filter. After filtration, the membrane was placed in a vacuum drying oven for vacuum drying to obtain a "three-dimensional through-pore structure composite conductive film doped with CNT and MXene" with a thickness of 80 μm and TPU as the matrix resin. The vacuum degree of the vacuum drying oven was -0.06 MPa, the drying temperature was 50℃, and the drying time was 1.5 h. The method for preparing the CNT monodisperse aqueous solution was adopted from the preparation method in patent CN2012104391772.

[0053] Example 3

[0054] In this embodiment of the invention, the PVDF resin was produced by Shanghai Sanai Fu New Material Technology Co., Ltd., the PVP resin was produced by Yatai United Chemical Co., Ltd., the MXene powder was Ti3C2 with a particle size of 200 mesh produced by Forsmann Technology (Beijing) Co., Ltd., the carbon nanotubes were multi-walled carbon nanotubes with a diameter of 8-15 nm and a length of 50 μm produced by Zhongke Nano Era Co., Ltd., and the N,N-dimethylacetamide (DMAc) solvent was produced by Sinopharm Chemical Reagent Co., Ltd.

[0055] A method for preparing a three-dimensional through-hole structure composite conductive film with PVDF as the matrix resin and doped CNTs and MXene, the specific steps of which are as follows:

[0056] Step 1: Add 4 ml of DMAc to 115 mg of MXene powder, grind evenly to form a paste, then add 296 ml of DMAc and stir evenly to obtain an MXene solution; ultrasonically exfoliate the MXene solution at 80 W for 50 min, centrifuge the ultrasonically treated MXene solution at 9000 rpm for 25 min, remove the supernatant, the precipitate is a high-concentration MXene dispersion, and store it under argon gas for later use;

[0057] Step 2: After vacuum drying 15g of PVDF and 5g of PVP, add them in portions to 80g of DMAc. Stir at 70℃ to obtain a PSU / PVP solution. After standing to defoam, add 5g of high-concentration MXene dispersion to 17g of PVDF / PVP resin solution. Stir at room temperature until the mixture is homogeneous to obtain an MXene / PVDF / PVP solution.

[0058] Step 3: Using a coating machine, adjust the coating thickness to 0.15 mm, coat the prepared MXene / PVDF / PVP solution onto a clean, scratch-free glass plate to prepare a thin film, quickly immerse the glass plate in deionized water at 35°C, wait for the film to detach from the glass plate, soak for 6 hours to obtain an MXene / PVDF porous membrane, transfer it to clean deionized water for storage and later use.

[0059] Step 4: Using an MXene / PVDF porous membrane as the filtration substrate, 500 ml of CNT monodisperse aqueous solution was uniformly filtered into the MXene / PVDF porous membrane using a vacuum filter. After filtration, the membrane was placed in a vacuum drying oven for vacuum drying to obtain a "three-dimensional through-pore structure composite conductive film doped with CNT and MXene" with a thickness of 97 μm and PVDF as the matrix resin. The vacuum degree of the vacuum drying oven was -0.06 MPa, the drying temperature was 60℃, and the drying time was 1 h. The method for preparing the CNT monodisperse aqueous solution was adopted from the preparation method in patent CN2012104391772.

Claims

1. A method for preparing a three-dimensional through-hole structure composite conductive thin film doped with CNTs and MXene, characterized in that, Includes the following steps: Step 1: MXene powder and organic solvent were mixed evenly at a mass-to-volume ratio of 1:(2.11-2.85). The mixture was then ultrasonically exfoliated at 80W for 20-60 minutes, followed by high-speed centrifugation at 7000-10000 rpm for 20-30 minutes to obtain a high-concentration MXene dispersion. This dispersion was stored under argon gas for later use. The organic solvent was selected from DMAc, DMF, and NMP. The MXene was Ti3C2. Step 2: After vacuum drying the resin and PVP, add them to an organic solvent and stir. Then, add the prepared high-concentration MXene dispersion and continue stirring until homogeneous to obtain an MXene / resin / PVP solution. The resin is selected from polysulfone, polyurethane, and polyvinylidene fluoride. The mass ratio of resin to PVP is 1:(0.2-0.8). The mass ratio of resin to organic solvent is 1:(3.1-9.1). The organic solvent is selected from DMAc, DMF, and NMP. Step 3: Coat the MXene / resin / PVP solution onto a clean glass plate to form a thin film, then quickly immerse the glass plate in deionized water and soak it to obtain an MXene / resin porous membrane. Step 4: Using MXene / resin porous membrane as the filtration substrate, CNT monodisperse aqueous solution is uniformly filtered into MXene / resin porous membrane. After vacuum drying, a three-dimensional through-pore structure composite conductive film with CNT and MXene doped is obtained with a thickness of 80-110 μm.

2. The method for preparing a three-dimensional through-hole structure composite conductive thin film doped with CNTs and MXene according to claim 1, characterized in that, The preparation process of the MXene / resin porous membrane in steps 2-3 specifically includes: (1) After vacuum drying of resin and PVP, add them to organic solvent and stir magnetically at 60-80℃ to obtain resin / PVP solution, and let stand to defoam. (2) Add the high-concentration MXene dispersion to the resin / PVP solution and stir magnetically at room temperature to obtain the MXene / resin / PVP solution; wherein the mass ratio of the high-concentration MXene dispersion to the resin / PVP solution is 5:(15-20). (3) Prepare a thin film by placing the MXene / resin / PVP solution on a clean, scratch-free glass plate, quickly immerse the glass plate in deionized water at 30-40℃, wait for the film to detach from the glass plate, soak for 6-8 hours, and obtain the MXene / resin porous membrane. Transfer it to clean deionized water for storage.

3. The method for preparing a three-dimensional through-hole structure composite conductive thin film doped with CNTs and MXene according to claim 1, characterized in that, In step 4, the CNT is a multi-walled carbon nanotube with a diameter of 8-15 nm and a length of 30-70 μm.

4. The method for preparing a three-dimensional through-hole structure composite conductive thin film doped with CNTs and MXene according to claim 1, characterized in that, In step 4, the vacuum degree of the vacuum drying oven is -0.06MPa, the drying temperature is 40-60℃, and the drying time is 1-2h.

5. A three-dimensional through-hole structure composite conductive film doped with CNTs and MXene, characterized in that, It is prepared by the preparation method according to any one of claims 1-4.

Citation Information

Patent Citations

  • MXene-based three-dimensional porous flexible self-supporting membrane, preparation method thereof and application of membrane in electrochemical adsorption of dyes

    CN112452299A

  • Self-supporting polyimide MXene flexible film as well as preparation method and application thereof

    CN114725380A